Performance Evaluation of Hybrid MQL-Brass Nano-Fluid Coolant on Aisi 304 SS for Efficient Machining Operation - Borokinni, Francis Olusesi; Bolaji, Bukola Olalekan; Olorunfemi, Bayode Julius; Bello, Kazeem Aderemi; Oginni, Olarewaju Thomas (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
Brass Nanofluid is a substance made from synthetic copper and zinc powder. It has outstanding mechanical, electrical, thermal and optical qualities employed in a variety of applications including, solar, touch screen, bison. The nanoparticles used in this study were developed from brass alloy which was locally sourced and machined to the required nano-size of 40 µm. A top-down strategy was used for the preparation of nanofluid and ball milling utilized to ground the brass alloy and sieved after grinding using a 40 µm sleeve. A double approach strategy was applied to prepare the nanofluid and the sonification process of brass nanofluid was conducted using ultra sonic equipment. The result shows that the light paraffin oil with varying concentration percentage of brass alloy and conventional cutting fluid (castrole oil) with varying concentration percentage of brass alloy display similar performance. Optimizing the additive ratio of nano particle provided better outcomes identified in the range of 2-10g with 200 ml of cutting fluid. This improves the surface roughness finish of machined part while inclusion of brass nano particle with cutting fluid improves the material removal rate, reduce the temperature and the cutting zone providing a guaranteed finish product compared to other base fluid.